Haemorrhagic cystitis following the administration of voriconazole in the treatment of central nervous system aspergillosis: a case report - Zhaohao Zeng; Hong Luo; Kunyu Huang; Lianfang Xue; Hui Liu; Xiaoting Li; Lu Wang; Haimei Cen; Wei Bi; Yu Zhang (Journal of International Medical Research)
Central nervous system aspergillosis (CNS-A) is a rare and fatal fungal infection. Voriconazole is the recommended treatment for CNS-A. The therapeutic effect of voriconazole is good, but its use is limited due to adverse reactions. This case report describes a 37-year-old male patient that had previously been diagnosed with acute lymphoblastic leukaemia. He had received immunosuppressive agents for 1 year following a haematopoietic bone marrow transplant. He presented with a 1-month history of left limb weakness as well as recurrent fever. Brain magnetic resonance imaging showed that he had multiple cerebral infarctions. Subsequently, he was diagnosed with CNS-A by metagenomic next-generation sequencing. Voriconazole was added to his treatment regimen, but it resulted in severe haemorrhagic cystitis and possibly bladder rupture. The dose of voriconazole was adjusted and reparative bladder surgery was undertaken immediately. Eventually, the patient was successfully treated with voriconazole and there was no recurrence of symptoms after 1 year of follow-up. Haemorrhagic cystitis is a rare adverse drug reaction associated with voriconazole use. Based on the experience with this current case, physicians should be aware of urinary tract complications with voriconazole including haemorrhagic cystitis.